Travellers, Connoisseurs, and Britons: Art Commentaries and National Discourse in the Travel Writings of Daniel Defoe and Tobias Smollett - Lipski, Jakub (Studia Anglica Posnaniensia, 2017)
This article seeks to explore the interrelationship of two facets characterising eighteenth-century travel writing – art commentaries and national discourse. It is demonstrated that one of the reasons behind the travellers’ repetitious attempts to fashion themselves as connoisseurs was a need to re-affirm their national identity. To this end it offers an analysis of two travel texts coming from two different political moments – Daniel Defoe’s A Tour thro’ the Whole Island of Great Britain (1724–1726), constituting an attempt to read the British as a “great” and prosperous nation after the union of 1707, and Tobias Smollett’s idiosyncratic Travels through France and Italy (1766), shedding light on the British attitude towards the South in the aftermath of the Seven Years’ War and at the outset of the cult of feeling in Britain. It will also be argued that the numerous art commentaries throughout the narratives had a political agenda and supported the national discourse underpinning the texts.